Ligand binding at the A-cluster in full-length or truncated acetyl-CoA synthase studied by X-ray absorption spectroscopy. - Peer Schrapers; Julia Ilina; Christina M Gregg; Stefan Mebs; Jae-Hun Jeoung; Holger Dau; Holger Dobbek; Michael Haumann (PLoS ONE)
Bacteria integrate CO2 reduction and acetyl coenzyme-A (CoA) synthesis in the Wood-Ljungdal pathway. The acetyl-CoA synthase (ACS) active site is a [4Fe4S]-[NiNi] complex (A-cluster). The dinickel site structure (with proximal, p, and distal, d, ions) was studied by X-ray absorption spectroscopy in ACS variants comprising all three protein domains or only the C-terminal domain with the A-cluster. Both variants showed two square-planar Ni(II) sites and an OH- bound at Ni(II)p in oxidized enzyme and a H2O at Ni(I)p in reduced enzyme; a Ni(I)p-CO species was induced by CO incubation and a Ni(II)-CH3- species with an additional water ligand by a methyl group donor. These findings render a direct effect of the N-terminal and middle domains on the A-cluster structure unlikely.